Measuring Quality in the First House of Quality with Target-Oriented Multiattribute Preference Analysis - Xin-Wei, Zhang; Shu-Rong, Tong; Eres, Hakki; Chun-Zhi, Li (2017 International Conference on Management Science and Engineering (ICMSE), 2017)
Quality is inherent in the Quality Function Deployment (QFD) and its building construct of house of quality. In QFD, customer needs are identified as inputs to the first house of quality and then transformed through several stages into various levels of parameters to design for quality. However, in most cases numerical measurement of quality is not appropriately deployed. An approach for measuring quality in the first house of quality is proposed in the paper using target-oriented multi-attribute preference analysis. Firstly, quality in the first house of quality is examined from the viewpoint of evaluated aggregate quality. Secondly, attributes are identified to measure the achievement of customer needs and customer expectations on attributes are defined according to their relevant sources. Thirdly, quality in the first house of quality is measured with target-oriented multi-attribute preference analysis. The application of the approach is demonstrated through demonstrating quality measurement of a simplified case of a commercial aircraft.